2003
DOI: 10.1016/j.mod.2003.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of a starfish Otx ortholog, AmOtx: a conserved role for Otx proteins in endoderm development that predates divergence of the eleutherozoa

Abstract: The sea urchin orthodenticle (Otx)-related transcription factor is an early activator of other endomesodermally expressed transcription factors. Its normal function is required for the development of the archenteron and to lock cells into endomesodermal fate. To determine if this is a basal Otx function in echinoderms we have studied the role of an Otx ortholog in a starfish, Asterina miniata. The patterns of AmOtx expression are found to be similar, in many details, to those reported for other indirectly deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 31 publications
2
68
0
Order By: Relevance
“…For example, during fruit fly development many genes are expressed at peak levels for a brief developmental period, while others increase gradually to a stable maximum (Arbeitman et al, 2002). Similarly complex patterns of differential gene expression have been observed during development of other species of marine invertebrates (Char et al, 1993;Marsh et al, 2000;Hinman et al, 2003). Differences in gene expression at a particular developmental stage might reflect differences in the timing of a developmental peak in expression, or differences in the overall level of expression throughout development.…”
Section: Discussionmentioning
confidence: 91%
“…For example, during fruit fly development many genes are expressed at peak levels for a brief developmental period, while others increase gradually to a stable maximum (Arbeitman et al, 2002). Similarly complex patterns of differential gene expression have been observed during development of other species of marine invertebrates (Char et al, 1993;Marsh et al, 2000;Hinman et al, 2003). Differences in gene expression at a particular developmental stage might reflect differences in the timing of a developmental peak in expression, or differences in the overall level of expression throughout development.…”
Section: Discussionmentioning
confidence: 91%
“…The embryogenesis and early larval development of echinoderms involve the interactions of regulatory, structural, and functional genes that, in some cases, are highly conserved even among distantly related echinoderm species (Hinman & Davidson, 2003a,b; Hinman, Nguyen, Cameron, et al., 2003; Hinman, Nguyen, & Davidson, 2003). However, differences in skeleton formation and embryonic territories specification in this group are the result of evolutionary changes, which include gene duplications, protein function diversification, and genes co‐opted to different functions (Dylus et al., 2016; Hinman & Davidson, 2007; Hinman, Nguyen, Cameron, et al., 2003; McCauley et al., 2010, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In echinoderms, for example, the unique combination of regulatory genes (e.g., transcription factors) in embryonic space and time contribute to shaping the regulatory program for larval skeletogenesis (Dylus et al., 2016; Gao & Davidson, 2008), endomesodermal (Peter & Davidson, 2010), and ectodermal specification (Nakata & Minokawa, 2009). Despite the differences in larval development in this group (e.g., pluteus‐, bipinnaria‐, and auricularia‐like larvae), comparisons of their GRN architectures have detected highly conserved orthologous regulatory genes among the extant echinoderm classes (Hinman & Davidson, 2003a,b; Hinman, Nguyen, Cameron, & Davidson, 2003; Hinman, Nguyen, & Davidson, 2003). While the network logic employed is the same in these organisms, the transcription factors underlying certain functions have been the subject of evolutionary change, resulting in gene duplications, protein function diversification, and regulatory genes co‐opted to different functions (Dylus et al., 2016; Hinman & Davidson, 2007; Hinman, Nguyen, Cameron, et al., 2003; McCauley, Weideman, & Hinman, 2010; McCauley, Wright, Exner, Kitazawa, & Hinman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The authors thus proposed that the regulatory logic of Brachyury may differ in Halocynthia and Ciona. Comparison between two distantly related echinoderm, the starfish A. miniata and the sea urchin S. purpuratus, revealed that although some gene regulatory networks have persisted unaltered since the Cambrian period, others have extensively diverged (Hinman et al, 2003). The comparative analysis of the Brachyury and Otx regulatory logics between ascidians suggests that a similar phenomenon may also have occurred in this phylum.…”
Section: Features Of the Otx Cis-regulatory Logic In Ascidiansmentioning
confidence: 93%